Higher education and public sector employment: evidence from Finnish data on twins. Issue 5 (2nd September 2016) - Maczulskij, Terhi
Abstract: Using data from Finland on twins, this paper examines the effect of labour quality, as measured by education, on the choice to work in the public sector. A distinction to previous studies is made by allowing controls of family background and genetics effects that could drive the positive relationship between higher education and public sector employment. The conditional (fixed effects) logit regression estimates indicate that highly qualified employees are more likely to seek public sector employment. The paper also utilizes the longitudinal structure of the data to examine whether the results vary over time. These results indicate that the association between public sector work and higher education is counter-cyclical. In other words, highly qualified workers are more likely to hold public service positions and to have greater access to public sector jobs during economic downturns.